Intrinsically disordered protein, DNA binding with one finger transcription factor (OsDOF27) implicates thermotolerance in yeast and rice - Gandass, Nishu; Kajal,; Salvi, Prafull (Frontiers in Plant Science, 2022)
Intrinsically disorder regions or proteins (IDRs or IDPs) constitute a large subset of the eukaryotic proteome, which challenges the protein structure-function paradigm. These IDPs lack a stable tertiary structure, yet they play a crucial role in the diverse biological process of plants. This study showcases the first report about the intrinsically disordered nature of a plant-specific DNA Binding with One Finger transcription factor (DOF-TF). Here, we have investigated the role of OsDOF27 and characterised it as an intrinsically disordered protein. Further, the molecular role of OsDOF27 in thermal stress tolerance has been elucidated. The qRT-PCR analysis revealed that OsDOF27 significantly upregulated under different abiotic stress treatments in rice, particularly under heat stress. The stress-responsive transcript induction of OsDOF27 was further corelated with enriched abiotic stress related cis-regulatory elements present in its promoter region. The invivo functional analysis of the potential role of OsDOF27 in thermotolerance was further studied in yeast and in planta. Ectopic expression of OsDOF27 in yeast implicates thermotolerance response. Further, the rice transgenic lines with overexpressing OsDOF27 revealed its positive role in mitigating heat stress tolerance. Collectively, this is the first report representing the intrinsically disorderedness in DOF-TF and its role in thermal stress response in rice.